Analysis of growth and yield in Plumbago spp. - Menon, Jalaja S.; Amma, S. Prasannakumari; Nybe, E.V. (Journal of Tropical Agriculture, 2006)
Studies on growth and yield of Plumbago rosea and Plumbago zeylanica were undertaken in the College of Horticulture, Kerala Agricultural University, Thrissur during 1995 to 1998. Studies on growth up to 18 months after planting revealed that the two species exhibited a linear pattern of growth. There was no significant difference in fresh root yield of the two species. However, P. rosea recorded 7.78 per cent higher yield than P. zeylanica at 18 months after planting. The dry root yield was found to be significantly higher in P. zeylanica and the percentage of increase in yield in P. rosea was 83.5. It was observed that retention of crop in the field up to 18 months increased dry root yield by 2.27 times in P. rosea and 2.01 times in P. zeylanica as compared to harvesting at 12 moths after planting.